AAV‐mediated delivery of an anti‐BACE1 VHH alleviates pathology in an Alzheimer's disease model - Marika Marino; Lujia Zhou; Melvin Y Rincon; Zsuzsanna Callaerts‐Vegh; Jens Verhaert; Jérôme Wahis; Eline Creemers; Lidia Yshii; Keimpe Wierda; Takashi Saito; Catherine Marneffe; Iryna Voytyuk; et al. (EMBO Molecular Medicine, 2022)
Abstract Single domain antibodies (VHHs) are potentially disruptive therapeutics, with important biological value for treatment of several diseases, including neurological disorders. However, VHHs have not been widely used in the central nervous system (CNS), largely because of their restricted blood–brain barrier (BBB) penetration. Here, we propose a gene transfer strategy based on BBB‐crossing adeno‐associated virus (AAV)‐based vectors to deliver VHH directly into the CNS. As a proof‐of‐concept, we explored the potential of AAV‐delivered VHH to inhibit BACE1, a well‐characterized target in Alzheimer’s disease. First, we generated a panel of VHHs targeting BACE1, one of which, VHH‐B9, shows high selectivity for BACE1 and efficacy in lowering BACE1 activity in vitro. We further demonstrate that a single systemic dose of AAV‐VHH‐B9 produces positive long‐term (12 months plus) effects on amyloid load, neuroinflammation, synaptic function, and cognitive performance, in the AppNL‐G‐F Alzheimer’s mouse model. These results constitute a novel therapeutic approach for neurodegenerative diseases, which is applicable to a range of CNS disease targets.